ANALISIS FAKTOR-FAKTOR RENDAHNYA KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA DI SMK SWASTA TERUNA PADANGSIDIMPUAN - Rahmat Hidayat; Eva Yanti Siregar; Rahmatika Elindra (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2022)
The purpose of this study was to analyze the factors of the low mathematical problem solving ability of students on Arithmetic Rows and Series materials at the Padangsidimpuan Teruna Private Vocational School. The researcher uses qualitative research methods with analytical techniques that include data reduction, data presentation and conclusions. Data collection methods in this study used tests, questionnaires and interviews. the data source is the 11th grade students of Padangsidimpuan Teruna Private Vocational School. Based on the results of the study, it can be concluded that students who do not have a poor level of problem solving ability do not have planning and evaluation skills. So that solving problems in Arithmetic Sequences and Series cannot be applied.